Court Interpreting in Indonesia: An Interdisciplinary Critical Review of Linguistic Accuracy and Legal Integrity in Foreign-Language Judicial Proceedings - Muhammad Fariq Heemal Attruk; Muhamad Irwan; Indra Rukmono; Reza Dipta Prayitna (Universitas Kristen Cipta Wacana, 2025)
The increasing involvement of foreign-language speakers and documents in Indonesian court proceedings has brought renewed attention to the role of court interpreting within the administration of justice. In judicial settings, interpreting does not merely facilitate communication but actively shapes how facts are constructed, understood, and evaluated by legal actors. This article presents an interdisciplinary Critical Literature Review that examines court interpreting practices in Indonesia by foregrounding the relationship between linguistic accuracy and legal integrity in foreign-language judicial proceedings. Focusing on Indonesia-focused primary studies, the review synthesizes findings from applied linguistics and legal scholarship to identify recurring issues in courtroom interpreting, including the procedural status of translated documents, the practical limits of verbatim accuracy, institutional constraints faced by interpreters, and divergent judicial approaches to language compliance. The analysis demonstrates that linguistic accuracy functions as a procedural and epistemic condition rather than a purely technical concern, with direct implications for evidentiary assessment and procedural fairness. At the same time, the review reveals a persistent gap between the epistemic responsibility borne by court interpreters and the limited regulatory and institutional frameworks governing their role in Indonesian courts. The article argues that strengthening legal integrity in foreign-language cases requires clearer standards for courtroom interpreting, improved institutional support, and sustained interdisciplinary engagement between linguists and legal practitioners to ensure that language mediation effectively safeguards due process in Indonesia’s increasingly multilingual judicial landscape.